Синтез, властивості та застосування в онкотерапії нанокомпозитів на основі гемцитабіну - Туранська, С. П.; Опанащук, Н. М.; Петрановська, А. Л.; Кусяк, Н. В.; Тарасюк, Б. І.; Горобець, С. В.; Туров, В. В.; Горбик, П. П.; Абрамов, М. В. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2019)
The aim of the work is to review scientific papers on the synthesis, study of properties and application of nanocomposites based on gemcitabine, promising for use in the targeted delivery method, in medicine, in particular oncotherapy. A generally recognized alternative to traditional chemotherapy with gemcitabine (GC) is the use of targeted delivery methods that allow one to create a therapeutic dose of the drug in a disease nidus, to carry out therapy at a much lower its total dose and minimize toxico-allergic reactions in patients. Currently, among the variety of modern methods of targeted drug delivery and local treatment of diseases at the level of organs, cells and genes, the methods have received the highest development using magnetosensitive nanostructures conjugated with antitumor agents of various mechanisms of action. Currently, the concept has been substantiated for chemical construction of magnetically sensitive nanocomposites (NC) with a multi-level hierarchical nanoarchitecture, which are characterized by the functions of "nanoclinics" and biomedical nanorobots: recognition of microbiological objects in biological environments; targeted drug delivery to specific cells and organs, and deposition; complex local chemo-, immuno-, neutron capture, hyperthermic, photodynamic therapy and magnetic resonance imaging diagnostics in real-time regime, detoxification of an organism by adsorption of cellular decomposition residues, viral particles, heavy metal ions, etc. and their removal using a magnetic field. For the manufacture of magnetically sensitive multifunctional NC, a considerable interest of researchers is drawn by core-shell type nanostructures based on single-domain magnetite (Fe3O4), which are characterized by a unique complex of physical, chemical and biological properties, the possibility to create magnetic liquids based on them, containing oncological remedies of various functional purpose and mechanisms of action. It has been shown that one of the main problems of modern antitumor therapy with gemcitabine is the toxicity and poor bioavailability of the drug. In recent years, an interest has been significantly increased to use the natural mechanisms of endocytosis and various types of nanostructures for delivering of drugs to tumors, involving ligands such as hormones, vitamins, and growth factors directed against tumor-associated receptors that are excessively present on the surface of tumor cells and have a limited distribution in normal tissues. Currently, using methods of modern nanotechnology, magnetically sensitive and non-magnetic conjugates are actively developed for targeted delivery of GC to malignant cells, which will reduce its systemic toxicity. The advantage gained by the drug conjugation on the surface of nanoparticles for drug delivery in vivo is the slow release of the drug, potentially providing a longer presence of the drug in the blood stream at the required level. A positive result of the use of hyperthermia in combination with the release of drugs can be an improvement in the patient's condition and a decrease in the frequency of drug administration. Despite a significant number of successful studies on the use of magnetic nanoparticles as a theranostic material, as well as repeated successful results in small animal models, they still do not satisfy clinical needs. However, upon reaching a high capacity in relation to the drug, increasing specificity and affinity for tumor cells, in a combination of imaging and multimodal local therapy, magnetic nanoparticles may become convenient for clinical use in the near future and significantly affect the effectiveness of cancer treatment.